2019
DOI: 10.1038/s41598-019-48953-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-based gas molecule adsorption of monolayer phosphorene under metal functionalization

Abstract: Using the first-principles calculation based on density functional theory (DFT), the adsorption properties of nitrogen-based gases molecules (NH 3 , NO, NO 2 ) on various metal (Li, Na, K, Rb, Cs, Ca, Sr, Ba, Ni, La, Tl) decorated phosphorene systems have been studied systematically. The results show that all metal decorations can improve the adsorption strength of phosphorene to nitrogen-based gases molecules except for Tl decoration. Especially, the adsorption en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Nugraha et al found that NO 2 and SO 2 molecules get adsorbed with high adsorption energy on ZnO(0002) surface [52]. Lei et al have reported that NO and NO 2 molecules get adsorbed with 2.47 and 3.73 eV adsorption energy, respectively, on La decorated phosphorene [53]. de Amorim et al have shown that CO, NO, and SO molecules get adsorbed on Ni 6 nanocluster with 2.18, 3.00, and 3.13 eV adsorption energy, respectively [54].…”
Section: Resultsmentioning
confidence: 99%
“…Nugraha et al found that NO 2 and SO 2 molecules get adsorbed with high adsorption energy on ZnO(0002) surface [52]. Lei et al have reported that NO and NO 2 molecules get adsorbed with 2.47 and 3.73 eV adsorption energy, respectively, on La decorated phosphorene [53]. de Amorim et al have shown that CO, NO, and SO molecules get adsorbed on Ni 6 nanocluster with 2.18, 3.00, and 3.13 eV adsorption energy, respectively [54].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, phosphorene shows an adsorption capacity of 4.8 mg g −1 for inorganic iAs III in contrast to graphene, which reaches 1.3 mg g −1 at pH=7 [31]. The adsorption strength on phosphorene is often stronger than graphene because the chemically active phosphorous atom makes it have stronger affinity interaction with the atoms or molecules [32]. Additionally, density functional theory (DFT) calculations show that phosphorene doping with transition metals (e.g., Fe, Ni, and Cu, Scheme 1e) enhances the adsorption capacity by a strong inner-sphere surface complexation of chemical nature reaching adsorption energies of up to ~2.0 eV [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lei et al. explored the NO 2 adsorption on metal‐doped phosphorene using first‐principles calculations and revealed that the strength of NO 2 adsorption on La‐doped phosphorene was greater than that on Li‐, Na‐, and K‐doped phosphorene 25 . Hydroxides 26 and metal oxides 27 have also been utilized for NO 2 adsorption studies.…”
Section: Introductionmentioning
confidence: 99%
“…24 Similarly, Lei et al explored the NO 2 adsorption on metal-doped phosphorene using first-principles calculations and revealed that the strength of NO 2 adsorption on La-doped phosphorene was greater than that on Li-, Na-, and K-doped phosphorene. 25 Hydroxides 26 and metal oxides 27 have also been utilized for NO 2 adsorption studies. For example, Shang et al reported that layered double hydroxides that include transition metals showed outstanding adsorption capacity for NO 2 .…”
Section: Introductionmentioning
confidence: 99%